How a Network Approach Has Advanced the Field of Plant Invasion Ecology - Emer, Carine [UNESP]; Timoteo, Sergio; Traveset, A.; Richardson, D. M. (Cabi Publishing-c A B Int, 2020)
Every organism on Earth, whether in natural or anthropogenic environments, is connected to a complex web of life, the famous 'entangled bank' coined by Darwin in 1859. Non-native species can integrate into local 'banks' by establishing novel associations with the resident species. In that context, network ecology has been an important tool to study the interactions of non-native species and the effects on recipient communities due to its ability to simultaneously investigate the assembly and disassembly of species interactions as well as their functional roles. Its visually appealing tools and relatively simple metrics gained momentum among scientists and are increasingly applied in different areas of ecology, from the more theoretical grounds to applied research on restoration and conservation. A network approach helps us to understand how plant invasions may or may not form novel species associations, how they change the structure of invaded communities, the outcomes for ecosystem functionality and, ultimately, the implications for the conservation of ecological interactions. Networks have been widely used on pollination studies, especially from temperate zones, unveiling their nested patterns and the mechanisms by which non-native plants integrate into local communities. Yet, very few papers have used network approaches to assess plant invasion effects in other systems such as plant-herbivore, plant-pathogen or seed-dispersal processes. Here we describe how joining network ecology with plant invasion biology started and how it has developed over the last few decades. We show the extent of its contribution, despite contradictory results and biases, to a better understanding of the role of non-native plant species in shaping community structure. Finally, we explore how it can be further improved to answer emerging questions.